Enola Holmes mystery. Volume 3, The case of the bizarre bouquets - Blasco, Serena (IDW Publishing, 2020)
Enola is still hiding from Sherlock and her other brother Mycroft, who want to place her in a boarding school since their mother's disappearance. Looking for a new disguise, she finds just what she needs in a theatrical costume shop. This time, no old woman or ingenious girl will do as she transforms herself into an elegant and refined lady. When she questions Mrs. Watson about her husband's disappearance, Enola notices a strange bouquet. It is here that she has the upper hand on Sherlock. Enola's mother taught her about the secret language of flowers. The meaning of the bouquet is "bad luck," "death," and "revenge"! Can she locate Dr. Watson in time?